2021
DOI: 10.1007/s10549-021-06470-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry study of tumor vascular normalization and anti-angiogenic effects of sunitinib versus bevacizumab prior to dose-dense doxorubicin/cyclophosphamide chemotherapy in HER2-negative breast cancer

Abstract: Purpose Tumor angiogenesis controlled predominantly by vascular endothelial growth factor and its receptor (VEGF-VEGFR) interaction plays a key role in the growth and propagation of cancer cells. However, the newly formed network of blood vessels is disorganized and leaky. Pre-treatment with anti-angiogenic agents can “normalize” the tumor vasculature allowing effective intra-tumoral delivery of standard chemotherapy. Immunohistochemistry (IHC) analysis was applied to investigate and compare the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…Indeed, a judicious use of angiogenesis inhibitors and in some cases a paradoxical promotion of new tumor blood vessels, can improve the delivery and efficacy of chemotherapeutic drugs. In one example, Sunitinib (a tyrosine kinase inhibitor with activity for VEGFRs) was found to increase tumor vessel normalization and, when combined with chemotherapy, resulted in a greater inhibition of tumor cell proliferation [ 305 ].…”
Section: New Concepts In the Field Of Angiogenesismentioning
confidence: 99%
“…Indeed, a judicious use of angiogenesis inhibitors and in some cases a paradoxical promotion of new tumor blood vessels, can improve the delivery and efficacy of chemotherapeutic drugs. In one example, Sunitinib (a tyrosine kinase inhibitor with activity for VEGFRs) was found to increase tumor vessel normalization and, when combined with chemotherapy, resulted in a greater inhibition of tumor cell proliferation [ 305 ].…”
Section: New Concepts In the Field Of Angiogenesismentioning
confidence: 99%
“…Patients with newly diagnosed HER2− breast cancer were enrolled into this prospective, Phase II open-label study of chemotherapy in combination with low-dose antiangiogenic agents to normalize tumor vasculature, conducted at the National University Cancer Institute, Singapore (NCIS) [ 14 ]. The study was approved by the institution’s ethics review board and all patients signed written informed consent (ClinicalTrials.gov identifier: NCT02790580).…”
Section: Methodsmentioning
confidence: 99%
“…Our group has previously studied the strategy of pre-treatment with low-dose anti-angiogenic agents to normalize tumor vasculature to improve intra-tumoral delivery of standard neoadjuvant chemotherapy in breast cancer in two clinical trials [ 13 , 14 ]. The first trial tested low-dose short-course sunitinib and confirmed vascular normalization on functional imaging and immunohistochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, trials employing pre-treatment of sunitinib before chemotherapy in breast cancer patients, demonstrated a statistically significant 12.46% increase in vascular normalisation index (VNI) compared to pre-treatment with bevacizumab ( 113 ). The VNI biomarker is defined by vessel permeability, volume and collagen IV plasma levels (relative to basement membrane thinning) which allows for quantification of vascular normalisation ( 114 , 115 ).…”
Section: Therapeutics Targeting the Tumour Vasculaturementioning
confidence: 99%
“…The VNI biomarker is defined by vessel permeability, volume and collagen IV plasma levels (relative to basement membrane thinning) which allows for quantification of vascular normalisation ( 114 , 115 ). The observed VNI therefore indicates anti-angiogenic pre-treatment may improve chemotherapeutic drug delivery, particularly in cancers where concurrent administration has not proved effective ( 113 ).…”
Section: Therapeutics Targeting the Tumour Vasculaturementioning
confidence: 99%